2020
DOI: 10.1213/ane.0000000000004191
|View full text |Cite
|
Sign up to set email alerts
|

Association of Intraoperative Ventilator Management With Postoperative Oxygenation, Pulmonary Complications, and Mortality

Abstract: BACKGROUND: “Lung-protective ventilation” describes a ventilation strategy involving low tidal volumes (VTs) and/or low driving pressure/plateau pressure and has been associated with improved outcomes after mechanical ventilation. We evaluated the association between intraoperative ventilation parameters (including positive end-expiratory pressure [PEEP], driving pressure, and VT) and 3 postoperative outcomes: (1) Pao 2/fractional inspired oxygen tension (Fio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Given these ranges, our cutoffs were selected by inspection of previously collected ventilation practice institutional data, targeting upper quartiles (approximately 75% compliance for each component) to ensure class balance between cases with LPV versus non-LPV and to improve multivariable model discrimination. 5,13,28,[38][39][40] Predicted body weight (PBW, in kg) was calculated as: 50 + 2.3 * (height (in) -60) for men; 45 + 2.3 * (height (in) -60) for women. 41 Modified airway driving pressure (ΔP) was calculated as (peak inspiratory pressure -PEEP).…”
Section: Exposure Variables -Lung-protective Ventilationmentioning
confidence: 99%
“…Given these ranges, our cutoffs were selected by inspection of previously collected ventilation practice institutional data, targeting upper quartiles (approximately 75% compliance for each component) to ensure class balance between cases with LPV versus non-LPV and to improve multivariable model discrimination. 5,13,28,[38][39][40] Predicted body weight (PBW, in kg) was calculated as: 50 + 2.3 * (height (in) -60) for men; 45 + 2.3 * (height (in) -60) for women. 41 Modified airway driving pressure (ΔP) was calculated as (peak inspiratory pressure -PEEP).…”
Section: Exposure Variables -Lung-protective Ventilationmentioning
confidence: 99%
“…Atelectasis is also one of the most commonly occurring pulmonary complication after GA and may affect postoperative recovery; indeed, atelectasis is detectable for as long as 4 days in the postoperative evaluation [ 82 ] and has been associated with occurrence of pneumonia [ 80 ]. In support of this hypothesis, two large retrospective studies showed that high intraoperative FIO 2 was associated with a dose-dependent manner in major respiratory complications and with a 30-day mortality rate [ 83 , 84 ]. These results are not confirmed in an RCT comparing two “fixed” FIO 2 rate (30% vs. 80%), where no benefit or harmful effects were showed [ 85 ].…”
Section: Fraction Of Inspired Oxygenmentioning
confidence: 98%
“…To create these model, we first used least absolute shrinkage and selection operator (LASSO) using the proc hpgenselect procedure in SAS to select variables for inclusion at each prediction window as previously described. 17…”
Section: Generalized Linear Modelingmentioning
confidence: 99%